Pemanfaatan Moda Gerobak Motor, Sebagai Sarana Peningkatan Produktivitas Dan Layanan Laundry Keliling Di Green Laundry Jombang (Fakultas Teknik, Universitas Brawijaya, 2025)
Green Laundry is a small business unit offering washing and ironing services based on weight (kilograms) in Jombang Regency. This business provides affordable washing and ironing services compared to existing laundry services while maintaining high-quality standards. With the slogan,